Cognitive Behavioral Therapy for Insomnia as Adjunctive Therapy to Antipsychotics in Schizophrenia: A Case Report - Izuhara, Muneto; Matsuda, Hiroyuki; Saito, Ami; Hayashida, Maiko; Miura, Syoko; Oh-Nishi, Arata; Azis, Ilhamuddin Abdul; Abdullah, Rostia Arianna; Tsuchie, Keiko; Araki, Tomoko; Ryousuke, Arauchi; Kanayama, Misako; et al. (Frontiers in Psychiatry, 2018)
The authors present the case of a 38-year-old man with schizophrenia and with severe insomnia, who attempted suicide twice during oral drug therapy with risperidone. The patient slept barely two or three hours per night, and he frequently took half days off from work due to excessive daytime sleepiness. As a maladaptive behavior to insomnia, he progressively spent more time lying in bed without sleeping, and he repeatedly thought about his memories, which were reconstructed from his hallucinations. His relatives and friends frequently noticed that his memories were not correct. Consequently, the patient did not trust his memory, and he began to think that the hallucinations controlled his life. During his insomniac state, he did not take antipsychotic drugs regularly because of his irregular meal schedule due to his excessive daytime sleepiness. The authors started cognitive behavioral therapy for insomnia (CBT-i) with aripiprazole long acting injection (LAI). CBT-i is needed to be tailored to the patient’s specific problems, as this case showed that the patient maladaptively use chlorpromazine as a painkiller, and he exercised in the middle of the night because he believed he can fall asleep soon after the exercise. During his CBT-i course, he learned how to evaluate and control his sleep. The patient, who originally wanted to be short sleeper, began to understand that adequate amounts of sleep would contribute to his quality of life. He finally stopped taking chlorpromazine and benzodiazepine as sleeping drugs while taking suvorexant 20 mg. Through CBT-i, he came to understand that poor sleep worsened his hallucinations, and consequently made his life miserable. He understood that good sleep eased his hallucinations, ameliorated his daytime sleepiness and improved his concentration during working hours. Thus, he was able to improve his self-esteem and self-efficacy by controlling his sleep. In this case report, the authors suggest that CBT-i can be an effective therapy for schizophrenia patients with insomnia to the same extent of other psychiatric and non-psychiatric patients.